Elevating Form over Substance: A Reply to Professors James Liebman, Jeffrey Fagan and Valerie West - Adam L. VanGrack (Washington University Law Quarterly, 2002)
VanGrack's recent Note, Serious Error with “Serious Error”: Repairing A Broken System of Capital Punishment, discussed problems that the author found with the study released in June 2000 by Professors James Liebman, Jeffrey Fagan, and Valerie West entitled A Broken System: Error Rates in Capital Cases. In this response, the author addresses a number of these concerns with the study’s authors in a public forum to elaborate on the previous comments and extinguish any misunderstandings they may have regarding any prior valid statements. While certain differences of interpretation in terms of form versus substance exist between the authors of A Broken System and VanGrack, the author's Note did not contain any misstatements, “inaccuracies,” or “statements with no credible support or basis.” Further, the fact that the Washington University Law Quarterly expressed “concern” over the authors’ letter to the journal’s Editor in Chief does not mean that the Law Quarterly or any person associated with the journal agrees with any of the authors’ assertions against the author's Note. Whether such assertions are valid or not, one would hope that an established journal would (1) express “concern” if certain peers claimed that the journal had published misstatements, and (2) address those claims directly and in a public forum. This Reply will address, in order, the three areas of the Note to which the authors of A Broken System refer in their Rejoinder. Part II will discuss the Note’s assertion that the lack of availability of the data from A Broken System is problematic. Part III will address possible replicability of the study. And Part IV will further elaborate on problems with A Broken System’s state-by-state analysis, as well as my Note’s references to Virginia. Finally, it is important to recognize that the authors’ semantic complaints over the use of certain terms or words do not address the significant substantive problems of A Broken System as discussed in the author's Note.
Keywords: Social sciences; Peer review (Professional performance); Law – Periodicals; Capital punishment